(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The important cultural events in an individual’s life from birth to death are grouped under the term “Samskar”. Commonly used meaning of the word “Samskar” is “Samskarohi gunantaradhanam”, means it is a process or procedure by which change and improvement in the qualities of a substance is brought about. In this context of the article, Samskar means the procedure which brings definitive positive changes in life for optimal survival of an individual. Samskaras introduce some essential qualities by means of qualitative improvement and some ritual conducts. In contemporary pediatrics the term growth and development are used to denote the maturation of body. While growth denotes quantitative change, the term development refers to qualitative change in body. Optimal growth and development during childhood is necessary for a healthy adult life. In ancient times on the occasion of performing various Samskaras at different ages the physician can assess the various aspects of growth and development of an individual. The number of Samskaras varies amongst Hindu Dharma Granthas (text books) and also in different communities as well. However sixteen in number which were put forward by Maharshi Dayanand. Among these eight Samskaras are performed during Balyavastha. The main aim of performing Samskaras are to provide the baby an optimal intrauterine and extra uterine life, to develop proper feeding habits and to ensure adequate nutrition. In the practice of Bala- Samskaras religious rituals holds great importance in the mental, physical, social, and spiritual development of a child. This article explores the concept of Bal-Samskaras in Ayurveda and emphasizing the significance of these rituals in shaping a person’s life.